Penguatan Literasi Media Digital di Pesantren Tradisional Alfathaniyah Kota Serang: Membangun Generasi Melek Teknologi dengan Nilai Keislaman - Ikhsan Ahmad; Iman Mukhroman; Rangga Galura Gumelar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Traditional pesantren is one of the educational institutions that has been born since 300 years ago and now lives in the digital era. How is digital literacy in traditional pesantren, such as ponpes Alfathaniyah? This is important to know, considering that digital media literacy is key in understanding the development and progress of today's civilisation. Therefore, the community service programme at Salafiyah Alfathaniyah Pesantren in Serang City aims to introduce and strengthen the culture of digital literacy through a series of training and mentoring. The programme method was carried out through a participatory approach with educational sessions, hands-on practice, and interactive discussions between presenters, pesantren caregivers, and students. The materials presented included an introduction to digital media, media ethics, basic skills in using technology, and how to filter information in accordance with Islamic principles. This programme was attended by all santri. The results of the activity showed an increase in santri's understanding and skills in using digital media critically, creatively, and responsibly. In addition, this programme also succeeded in building awareness of the importance of maintaining Islamic manners in digital interactions. This digital media literacy strengthening programme is expected to be a sustainable model to be implemented in other pesantren, in order to prepare young people who are adaptive to technological developments without ignoring their Islamic identity.